2010
DOI: 10.1257/aer.100.1.557
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Time Preferences: Linking Experimental and Household Survey Data from Vietnam

Abstract: We conducted experiments in Vietnamese villages to determine the predictors of risk and time preferences. In villages with higher mean income, people are less loss-averse and more patient. Household income is correlated with patience but not with risk. We expand measurements of risk and time preferences beyond expected utility and exponential discounting, replacing those models with prospect theory and a three-parameter hyperbolic discounting model. Comparable risk parameter estimates have been found for Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

53
467
12
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 866 publications
(537 citation statements)
references
References 32 publications
53
467
12
5
Order By: Relevance
“…Our article is complementary to the recent study of Tanaka, Camerer and Nguyen (2010) who conducted risk and time experiments with rural villagers in Vietnam and found that wealthier villagers are less loss averse and more patient.…”
mentioning
confidence: 48%
See 3 more Smart Citations
“…Our article is complementary to the recent study of Tanaka, Camerer and Nguyen (2010) who conducted risk and time experiments with rural villagers in Vietnam and found that wealthier villagers are less loss averse and more patient.…”
mentioning
confidence: 48%
“…Most of these studies were carried out in developed countries, e.g. Denmark (Andersen et al 2008) or Japan (Ida and Goto 2009). One study that jointly explores risk and time preferences carried out in the developing world is that of Tanaka, Camerer and Nguyen (2010), who conducted experiments with rural villagers in Vietnam. They expanded the measurements of risk preferences beyond the concavity of the utility function and incorporated gains and losses through employing prospect theory (Kahneman & Tversky 1979;Tversky & Kahneman 1992).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 3 percent of participants chose not to answer at least one of the questions. 12 The risk aversion elicitation task was a modified version of the one used in Tanaka, Camerer and Nguyen (2010). Subjects were presented with a list of 10 choices between two lotteries.…”
Section: Design and Proceduresmentioning
confidence: 99%